Quality of Life of Children with Asthma and Their Caregivers: A Study at a Single Tertiary Care Centre in Northern Sri Lanka - Umasankar, N.; Sathees, T.; Sathiadas, M.G. (My University, 2024)
Asthma is the most prevalent chronic disease among children, representing a leading cause of paediatric morbidity and healthcare utilisation. It profoundly impacts various aspects of children’s quality of life and the quality of life of their caregivers. This study aims to assess the quality of life experienced by children with asthma and their caregivers and to determine the association between asthma control and quality of life. The children aged 6 to 16 years with asthma under the care of paediatric clinics at Teaching Hospital Jaffna and their caregivers were recruited. Data were collected through an interviewer-administered questionnaire. Pearson correlation coefficient was used to assess the correlations between asthma score and quality of life, and a linear regression was done to identify whether the asthma score can predict the child’s quality of life. Ninety-nine children and their caregivers participated in the study. Asthma was more prevalent among boys (54.5%). The mean age of children was 115.5± 31.6 months. The mean score on the childhood asthma control test was 19 ±4.05. The child-reported mean quality of life score was 74.47±10.05. Overall quality of life score was significantly diminished in children with uncontrolled asthma (p=0.003). There was a weak, positive correlation between the child’s total quality of life score and the asthma score. (r=0.25, p=0.006) In conclusion, this study highlights that asthma exerts a significant impact on children’s quality of life, particularly when the condition remains uncontrolled. The weak, positive correlation between the child’s asthma control score and total QoL score indicates that while asthma severity affects QoL, it is not the sole determinant
Keywords: Asthma; Quality of life; Children; PedsQL; Caregivers